Quantifying Craniometric Change Early After Fronto-Orbital Advancement in Metopic Synostosis. Issue 7 (October 2016) - Graf, Alexander R.; Klement, Kristen A.; Denny, Arlen D.
Abstract : Abstract: Frontal orbital advancement (FOA) for metopic synostosis results in cranial vault expansion, supporting underlying growth of the developing brain and improving head shape. Previous studies have shown that FOA in younger infants leads to a greater incidence of long-term growth restriction of intracranial volume; however, it is still unknown as to whether this is due to undercorrection at the time of surgery versus primary suture pathology. The purpose of our study is to provide a method for objective analyses of intracranial volumes in the early post-FOA period. A retrospective chart review was conducted on patients who underwent FOA over a 10-year period by a single surgeon. Data collected included patient characteristics and clinical outcomes. Radiological analysis of intracranial volumes pre- and post-FOA was determined using Amira volume-rendering software. Average increase in intracranial volume at 6 weeks post-FOA was 139.27 mL (80.01–225.25 mL) with average relative cranial vault expansion of 18.1% (3.3–48%). Patients who underwent FOA older than 12 months of age had an average increase in intracranial volume of 8.5% (3.3–13.1%). Patients younger than 12 months had a statistically higher average increase of 25% (12.8–48%). Frontal orbital advancement effectively increases intracranial volume in patients with metopic synostosis. When compared with older patients, patients younger than 1 year of age have a greater relative increase in intracranial volume in the immediate postoperative period. Quantifying cranial vault expansion after FOA can assist surgeons in surgical planning as well as in measuring and monitoring clinical outcomes within and across craniofacial centers regardless of technique.